Status of the DOM electronics. (27th October 2021) - Real, D.; Calvo, D.; van Beveren, V.; Musico, P.; Pellegini, G.; Jansweijer, P.; Colonges, S.; Chiarusi, T.; Bozza, C.; Nicolau, C.; Díaz, A.; Filippini, F.; et al.
Abstract: The KM3NeT collaboration has already produced electronics to assemble more than one thousand digital optical modules, which have started to be deployed at the bottom of the Mediterranean Sea. An upgrade of the electronics is currently underway, expecting to have a revision of it by end of 2021. Here we describe the main improvements added to the digital optical module electronics, including the new high reliability transceiver in the central logic board and the increased efficiency in the power board.